2010
DOI: 10.1016/j.neuroimage.2010.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A study of the reproducibility and etiology of diffusion anisotropy differences in developmental stuttering: A potential role for impaired myelination

Abstract: Several diffusion tensor imaging (DTI) studies have reported fractional anisotropy (FA) reductions within the left perisylvian white matter (WM) of persistent developmental stutterers (PSs). However, these studies have not reached the same conclusions in regard to the presence, spatial distribution (focal/ diffuse), and directionality (elevated/reduced) of FA differences outside of the left perisylvian region. In addition, supplemental DTI measures (axial and radial diffusivities, diffusion trace) have yet to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
116
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 71 publications
(140 reference statements)
13
116
1
5
Order By: Relevance
“…Although this is a small study, it was conducted with eight PWS who displayed greatly different levels of severity of stuttering (see earlier), 3 and with a predefined large effect size within each individual. It is acknowledged that the present DSI study needs to be replicated across different populations of PWS, especially those who no longer stutter.Previous DTI studies have found low FA values in regions approximating the arcuate fasciculus in the present study (Chang et al, 2008;Chang & Zhu, 2013;Connally et al, 2014;Cykowski et al, 2010;Sommer et al, 2002;Watkins et al, 2008). However, only Connally et al (2014 3 3 In previous DTI studies, investigators have attempted to find correlations between WM abnormalities and stuttering severity.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Although this is a small study, it was conducted with eight PWS who displayed greatly different levels of severity of stuttering (see earlier), 3 and with a predefined large effect size within each individual. It is acknowledged that the present DSI study needs to be replicated across different populations of PWS, especially those who no longer stutter.Previous DTI studies have found low FA values in regions approximating the arcuate fasciculus in the present study (Chang et al, 2008;Chang & Zhu, 2013;Connally et al, 2014;Cykowski et al, 2010;Sommer et al, 2002;Watkins et al, 2008). However, only Connally et al (2014 3 3 In previous DTI studies, investigators have attempted to find correlations between WM abnormalities and stuttering severity.…”
supporting
confidence: 59%
“…What the %SS data do show, however, is that each PWS did display stuttering across three widely used speaking tasks. It is worth noting that some previous attempts to find correlations between stuttering frequency or severity scores and WM have been generally unsuccessful (e.g., Cykowski et al, 2010;Chang et al, 2008 Cykowski et al (2010) actually favored superior longitudinal fasciculus rather than arcuate fasciculus as the site of low FA values. Furthermore, no DTI study of PWS has reported evidence consistent with the presence of an excessive left temporo-striatal tract.…”
mentioning
confidence: 99%
“…Packman (2012) has proposed a model of developmental stuttering whose central hypothesis is that the fundamental cause of the disorder is a neural deficit. This hypothesis is consistent with the findings of many recent studies which have reported structural and functional abnormalities in the brains of people who stutter (Chang, Erickson, Ambrose, Hasegawa-Johnson & Ludlow, 2008;Chang, Horwitz, Ostuni, Reynolds & Ludlow, 2011;Cykowski, Fox, Ingham, Ingham & Robin, 2010;Watkins, Smith, Davis & Howell, 2008). One risk factor for abnormal neural development is birth weight (Walhovd, Fjell, Brown, et al, 2012).…”
Section: Introductionsupporting
confidence: 90%
“…36 The conclusion that there is a left PO anomaly is also consistent with previous evidence which shows that the structural anomaly of PDS is neurodevelopment-related. 17,29,30 A further observation is that overactivations were not found in the right frontal operculum/ anterior insula. 2 The overactivations have been suggested as compensations to stuttering.…”
Section: Figurementioning
confidence: 91%
“…3,17,29,30 Other studies have also shown functional anomalies and structural disconnections in regions that surround, or are connected with, the left PO in such patients. 5,6,8,31 Moreover, the reduced gray matter volume and functional anomalies in the left IFC seem to be associated with high risk of childhood stuttering, 9,30 whereas the reduced white matter integrity around the left PO seems to be associated with the persistence of stuttering.…”
Section: Figurementioning
confidence: 93%